2005
DOI: 10.1080/08916930400022590
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to heterogeneous nuclear ribonucleoproteins

Abstract: Heterogeneous nuclear ribonucleoproteins (hnRNPs) are among the most abundant proteins in the eukaryotic cell nucleus and play a direct role in several aspects of the RNA life including splicing, export of the mature RNAs and translation. To date, approximately 30 proteins have been identified. A growing body of evidence points to hnRNPs as an important target of the autoimmune response in rheumatic diseases. Autoantibodies to A and B proteins of the hnRNP complex have been detected in late 1980s in rheumatoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 4 publications
0
24
0
3
Order By: Relevance
“…Several different hnRNP proteins (A1, A2, B, C, I, K, and R) have been described as autoantigens, as reviewed by Caporali et al (27 ). Antibodies to hnRNP A1 as well as antibodies to hnRNP A2, and its alternatively spliced variants B1 and B2, (the RA33 complex) have been described in RA, SLE, and MCTD (27,31,32 ). Anti-hnRNP I antibodies seem to be associated with (pre)-systemic sclerosis (33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different hnRNP proteins (A1, A2, B, C, I, K, and R) have been described as autoantigens, as reviewed by Caporali et al (27 ). Antibodies to hnRNP A1 as well as antibodies to hnRNP A2, and its alternatively spliced variants B1 and B2, (the RA33 complex) have been described in RA, SLE, and MCTD (27,31,32 ). Anti-hnRNP I antibodies seem to be associated with (pre)-systemic sclerosis (33 ).…”
Section: Discussionmentioning
confidence: 99%
“…They mainly play a role in processing of precursor mRNA, but are also involved in telomeric DNA synthesis and cellular apoptotic processes (27)(28)(29). hnRNPs are composed of at least 1 RNA recognition motif, also termed the RNA-binding domain.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent identification and genecloning analysis showed that certain protein spots were in fact different isoforms generated from the same gene [39] with a total of 19 hnRNP genes identified. These proteins mainly function in the processing of precursor mRNA, but are also involved in telomeric DNA synthesis and apoptotic processes [40,41]. Through such functions, this family of proteins could potentially regulate tumorigenesis.…”
Section: Comparative Serum Analysis For Cts mentioning
confidence: 99%
“…Thus, high-titre antibodies to the U1 snRNP are considered as marker for MCTD, and antibodies to the Sm proteins (named for Smith, the patient the antigen was first discovered in; ie, the core proteins common to all spliceosomal snRNPs) are generated almost exclusively by patients with SLE 3 4. In addition to snRNP proteins some hnRNPs have also been identified as antigenic targets 5 6. These antigens are not only recognised by autoantibodies from patients with SLE and MCTD but also by patients with other rheumatic diseases including rheumatoid arthritis (RA).…”
mentioning
confidence: 99%